Preparation method of high-strength, high-hardness, wear-resistant and high-entropy alloy coating
Through the combination of ultrasonic surface deep rolling and constant temperature annealing, the high-entropy alloy coating prepared by direct laser energy deposition is post-treated to form a microstructure structure in which gradient nanoheterogeneity and nanoprecipitation are composited, which solves the existence of pores in the coating. The defects such as inclusion and rough surface problems have significantly improved their strength, hardness and wear resistance.
Patent Information
- Application Number
- CN202411548802.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
The high-entropy alloy coating prepared by direct laser energy deposition has defects such as pores and inclusions, which limits the performance of its mechanical properties. At the same time, the surface is rough and difficult to apply directly. In addition, improving the multi-performance of the coating requires simultaneously improving the overall performance and surface quality.
The high-entropy alloy coating prepared by direct energy deposition was post-treated by combining ultrasonic surface deep rolling and constant temperature annealing to form a microstructure structure in which gradient nanoheterogeneity and nanoprecipitation were composited.
It significantly improves the strength, hardness and wear resistance of high entropy alloy coatings, reduces residual stress, and has a smooth surface, which is suitable for parts with high surface quality and high dimensional stability requirements.
Smart Images

Figure CN119407192A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating. Background Art
[0002] High entropy alloys are characterized by the composition of at least five main metal elements and have attracted increasing attention because of the great possibilities they provide in alloy composition design, microstructure adjustment, and performance regulation. As a structural metal material with application prospects, high entropy alloys have good strength and ductility in a wide temperature range, high fatigue and creep resistance, excellent corrosion resistance and wear resistance, and other special properties.
[0003] At present, the main production technologies of high entropy alloys are still vacuum arc melting and traditional induction melting. However, when vacuum arc melting and traditional induction melting are used, in order to achieve a relatively homogeneous microstructure distribution, the high entropy alloy is usually required to be remelted multiple times, and subsequent heat treatment and other process flows are also required. This preparation method has huge production costs and limited production efficiency, which is not conducive to the processing of engineering parts with complex geometric shapes, and also brings huge challenges to the industrialization of high entropy alloys. The preparation of high entropy alloy coatings on low-cost metal substrates has the advantages of outstanding wear resistance, enhanced hardness, and strong corrosion resistance, which is conducive to solving the production problems of vacuum arc melting and traditional induction melting, such as huge costs and limited efficiency. In recent years, additive manufacturing, as a revolutionary technology, has also promoted the research and development of high entropy alloy coatings. In particular, laser direct energy deposition, as an additive manufacturing process, has the advantages of saving time, saving material costs, and strong bonding between the coating and the metal substrate. It is expected to directly prepare high entropy alloy coatings in less time and prepare high entropy alloy coatings with good mechanical properties.
[0004] Although the strength, hardness, and wear resistance of laser direct energy deposition high-entropy alloy coatings have been improved to a certain extent compared to their traditional manufacturing materials, they still lag behind the growing engineering needs. For high-entropy alloys prepared by laser direct energy deposition, it is difficult to avoid defects such as pores and inclusions during the printing process, which limits the performance of their own mechanical properties; in addition, high-entropy alloys prepared by laser direct energy deposition often have a rough surface and cannot be directly applied in most cases. Improving the strength, hardness, wear resistance and other properties of the coating at the same time not only requires the improvement of the overall performance, but also places extremely high demands on the surface quality and surface properties. How to improve the multiple properties of direct energy deposition high-entropy alloy coatings through a technical strategy is still a major technical problem currently faced. Summary of the invention
[0005] The present invention provides a method for preparing a high-strength, high-hardness, and wear-resistant high-entropy alloy coating, specifically, post-treating the high-entropy alloy coating prepared by direct energy deposition through a combined method of ultrasonic surface deep rolling and constant temperature annealing, thereby obtaining a microstructure of a gradient nano-heterogeneous and nano-precipitated phase composite, thereby achieving a significant improvement in the strength, hardness, and wear resistance of the coating.
[0006] The technical means adopted by the present invention are as follows:
[0007] A method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating comprises the following steps:
[0008] S1. Machining and cleaning the substrate.
[0009] Use milling machines and other mechanical processing methods to obtain a substrate with a smooth surface; use a grinder or sandpaper to further grind the surface of the substrate until it is smooth and bright. Further use more than 95% alcohol to thoroughly clean the substrate.
[0010] S2. Using high entropy alloy powder, laser direct energy deposition is performed on the base plate to prepare a high entropy alloy coating.
[0011] Furthermore, the particle size of the high entropy alloy powder is 45 to 105 μm.
[0012] Furthermore, the atomic percentage composition of the high entropy alloy powder is Al x CoFeCoNi, where the value of x ranges from 0 to 1.5.
[0013] Furthermore, the laser power is 1000-4000W, the scanning speed is 4-10mm / s, the spot diameter is 1-8mm, and the overlap rate is 15%-55%. A crack-free and uniform high entropy alloy coating is prepared.
[0014] S3. Mechanically polish and clean the surface of the high entropy alloy coating.
[0015] Use a grinder or sandpaper to further grind the coating surface until it is smooth and bright. Then use more than 95% alcohol to thoroughly clean the substrate.
[0016] S4. The coating is treated by ultrasonic surface deep rolling technology to obtain a high entropy alloy coating with a gradient heterogeneous structure.
[0017] Furthermore, the static load of the ultrasonic surface deep rolling is 400-20000N, the frequency is 20-30kHz, the amplitude is 3-20μm, the rolling speed is 0.1-10m / min, the rolling interval is 0.01-0.5mm, the ball diameter is 4-20mm, and the rolling is 1-6 times.
[0018] Furthermore, during the ultrasonic surface deep rolling process, the ball's cutting direction is perpendicular to the laser direct energy deposition direction, and is cooled and lubricated by coolant or cooling oil. A cold source such as liquid nitrogen may also be used for more effective cooling.
[0019] S5. The high entropy alloy coating after ultrasonic surface deep rolling treatment is further treated by constant temperature annealing to form a nano-precipitation phase and optimize the residual stress.
[0020] Furthermore, the temperature range of the constant temperature annealing is 400-700° C., and the holding time is 1-50 hours.
[0021] Furthermore, the constant temperature annealing is performed in a muffle furnace, or a vacuum annealing furnace to reduce surface oxidation.
[0022] S6: Through the above steps, a composite microstructure of gradient heterostructure and nano-precipitation is obtained in the high entropy alloy coating.
[0023] The combined modification method of ultrasonic surface deep rolling and constant temperature annealing of the direct energy deposition high entropy alloy coating provided by the present invention has the following beneficial effects:
[0024] 1. The obtained high-entropy alloy coating has high strength, high hardness and high wear resistance, low residual stress and smooth coating surface, and can be directly applied to parts with high surface quality and high dimensional stability requirements.
[0025] 2. Through the combined process, a composite microstructure of gradient heterogeneous structure and nano-precipitation is obtained in the high-entropy alloy. Its characteristics are that the grain size gradually increases from the surface to the inside, the surface grains are refined to the nanoscale, and a dispersed precipitation phase is formed inside the coating, thereby improving the strength, hardness and wear resistance of the coating.
[0026] 3. The process has strong applicability and can be extended to high-entropy alloy coatings of other components. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0028] Attached Figure 1 It is a process flow chart of a method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating of the present invention;
[0029] Attached Figure 2 is a cross-sectional optical microscope image of the laser direct energy deposition high entropy alloy coating in Example 1;
[0030] Attached Figure 3 is a cross-sectional optical microscope image of the high entropy alloy coating after ultrasonic surface deep rolling in Example 2;
[0031] Attached Figure 4 This is a cross-sectional transmission microscope image of the high entropy alloy coating after ultrasonic surface deep rolling in Example 2. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] Embodiment 1:
[0034] As shown in the figure, the size is 50×100×30mm 3 27SiMn steel was used as the substrate and Al 0.5 The specific implementation process of CrFeCoNi high entropy alloy coating is as follows:
[0035] S1. Mechanical grinding and cleaning of 27SiMn steel plate:
[0036] Use 800-grit sandpaper to mechanically grind and polish the surface of the 27SiMn steel plate until it is smooth and bright. After mechanical grinding and polishing, the metal powder, rust products, dust, oil stains, etc. attached to the surface of the base plate are thoroughly cleaned with alcohol with a concentration of more than 95%, so that the base plate is basically clean and tidy, and then the surface of the base plate is dried with cold air from a hair dryer.
[0037] S2, using Al 0.5 CrFeCoNi metal powder was deposited by laser direct energy deposition on 27SiMn steel plate to prepare high entropy alloy coating:
[0038] The Al2O3 with a particle size of 45 to 105 μm produced by Beijing Longbang New Material Technology Co., Ltd. 0.5 CrFeCoNi metal powder. Using the laser direct energy deposition equipment of Highlaser Optoelectronic Technology Co., Ltd., in single-layer mode, the specific processing parameters used are: laser power of 3200W, scanning speed of 8mm / s, spot diameter of 5mm, overlap rate of 25%. A crack-free and uniform high-entropy alloy coating was prepared, with a coating thickness of about 1mm and a coating porosity of 0.5%.
[0039] S3. Mechanically polish and clean the surface of the high entropy alloy coating:
[0040] Use 800-grit sandpaper to mechanically polish the surface of the high-entropy alloy coating until it is smooth and bright. After mechanical polishing, the metal powder, rust products, dust, oil stains, etc. attached to the surface of the high-entropy alloy coating are thoroughly cleaned with alcohol with a concentration of more than 95%, so that the high-entropy alloy coating is basically clean and tidy, and then the surface of the high-entropy alloy coating is dried with cold air from a hair dryer.
[0041] Al prepared by laser direct energy deposition 0.5 Cross-sectional optical microscopy of CrFeCoNi high entropy alloy coating Figure 2 As shown, the cross section has obvious pores and the largest grain size is about 79.7μm. The high entropy alloy coating was cut off by an electric spark wire cutting machine, and a room temperature uniaxial tensile test was performed. The results showed that the yield strength of the high entropy alloy coating prepared by laser direct energy deposition was 488MPa; the ultimate tensile strength was 784MPa; and the elongation was 23.2%. The surface hardness of the high entropy alloy coating was measured by micro-Vickers hardness. The experiment used a force of 300g and a holding time of 15s. The results showed that the average surface hardness of the high entropy alloy coating prepared by laser direct energy deposition was 383.1HV. The wear resistance of the high entropy alloy coating was measured by a linear reciprocating sliding friction test. The results showed that the wear volume of the high entropy alloy coating prepared by laser direct energy deposition was 4.4×10 -3 mm 3 .
[0042] Embodiment 2:
[0043] As shown in the figure, the Al prepared by direct energy deposition is prepared by combining ultrasonic surface deep rolling technology and constant temperature annealing process. 0.5 The CrFeCoNi high entropy alloy coating is post-treated. This embodiment is the same as steps S1, S2 and S3 of embodiment 1, except that the following steps S4 and S5 are added.
[0044] S4. Ultrasonic surface deep rolling technology is used to further strengthen the high entropy alloy coating and improve the flatness of the alloy surface:
[0045] The material to be rolled is fixed on the machine tool, and the surface of the high entropy alloy coating is processed by a numerically controlled ultrasonic rolling device. The specific parameters of the ultrasonic surface deep rolling technology used in the present invention include a static load of 1200N, a frequency of ~22kHz, an amplitude of ~5μm, a rolling speed of 1.2m / min, a rolling interval of 0.1mm, and a ball diameter of 14mm. During the ultrasonic surface deep rolling process, the ball's cutting direction is perpendicular to the laser direct energy deposition direction, and the high entropy alloy coating surface is cooled by spraying liquid nitrogen.
[0046] S5. Further improve the coating performance through constant temperature annealing process.
[0047] After the ultrasonic surface deep rolling process, the high entropy alloy was placed in a muffle furnace, heated to 650°C at a heating rate of 10°C / min, kept at a constant temperature for one hour, and then water-cooled.
[0048] Al after ultrasonic surface deep rolling 0.5 Cross-sectional optical microscopy of CrFeCoNi high entropy alloy coating Figure 3 As shown, cross-sectional transmission microscopy Figure 4 As shown, the cross section is complete, without obvious voids, and the microstructure gradually refines from the inside to the surface, presenting a gradient heterogeneous structure. The high entropy alloy coating was cut off with an electric spark wire cutting machine, and a room temperature uniaxial tensile test was performed. The results showed that the yield strength of the high entropy alloy coating after ultrasonic surface deep rolling was 1163MPa; the ultimate tensile strength was 1458MPa; the elongation was 5.1%, which was significantly improved compared with the high entropy alloy coating after ultrasonic surface deep rolling in Example 1. The surface hardness of the high entropy alloy coating was measured by micro-Vickers hardness. The experiment used 300 forces and a holding time of 15s. The results showed that the average surface hardness of the high entropy alloy coating after ultrasonic surface deep rolling was 531.7HV, which was significantly improved compared with the high entropy alloy coating after ultrasonic surface deep rolling in Example 1. The wear resistance of the high entropy alloy coating was measured by a linear reciprocating sliding friction test. The results showed that the wear volume of the high entropy alloy coating after ultrasonic surface deep rolling was 1.7×10 -3 mm 3 Compared with Example 1, the wear resistance of the high entropy alloy coating after ultrasonic surface deep rolling is significantly improved.
[0049]
Claims
1. A method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating, characterized in that: The steps include: S1. Machining and cleaning the substrate; S2, using high entropy alloy powder, laser direct energy deposition is performed on the base plate to prepare a high entropy alloy coating; S3, mechanically grinding and cleaning the surface of the high entropy alloy coating; S4, using ultrasonic surface deep rolling technology to treat the coating to obtain a high entropy alloy coating with a gradient heterogeneous structure; S5, further treating the high entropy alloy coating after ultrasonic surface deep rolling treatment by constant temperature annealing to form a nano-precipitated phase and optimize the residual stress; S6. Through the above steps, a composite microstructure of gradient heterogeneous structure and nano-precipitation is obtained in the high entropy alloy coating.
2. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: In step S1, a milling machine or other mechanical processing method is used to obtain a substrate with a smooth surface; a grinder or sandpaper is used to further grind the substrate surface until it is smooth and bright, and then the substrate surface is thoroughly cleaned.
3. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: The particle size of the high entropy alloy powder used in step S2 is 45-105 μm.
4. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: The atomic percentage composition of the high entropy alloy powder used in step S2 is Al x CoFeCoNi, where the value of x ranges from 0 to 1.
5.
5. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: In step S2, the laser direct energy deposition uses a laser power of 1000-4000W, a scanning speed of 4-10mm / s, a spot diameter of 1-8mm, and an overlap rate of 15%-55%, thereby preparing a crack-free and uniform high-entropy alloy coating.
6. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: In step S3, the coating surface is further ground by a grinder or sandpaper until it is smooth and bright, and the high entropy alloy coating surface is thoroughly cleaned.
7. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: The processing parameters used in the ultrasonic surface deep rolling technology in step S4 are: static load of 400-20000N, frequency of 20-30kHz, amplitude of 3-20μm, rolling speed of 0.1-10m / min, rolling interval of 0.01-0.5mm, ball diameter of 4-20mm, and rolling 1-6 times.
8. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: In the ultrasonic surface deep rolling process of step S4, the cutting direction of the ball is perpendicular to the laser direct energy deposition direction of the high entropy alloy coating.
9. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: In the ultrasonic surface deep rolling process of step S4, cooling liquid or cooling oil is used for cooling and lubrication, and a cold source such as liquid nitrogen can also be used for more effective cooling.
10. The method for preparing a high-strength, high-hardness, wear-resistant high-entropy alloy coating according to claim 1, characterized in that: In step S5, the constant temperature annealing process adopts a high temperature muffle furnace or a vacuum annealing furnace, the temperature range is 400-700° C., and the insulation time is 1-50 hours.